The betA/B genes as a key factor in Cronobacter sakazakii survival under desiccation stress - Y. Yang; W. Wang; X. Meng; B. Niu; J. Yang; Q. Chen (Journal of Dairy Science, 2025)
ABSTRACT: Cronobacter is capable of long-term survival in dry environments such as powdered milk, which poses a health hazard to infants. To study the relationship between pathways and phenotypes from complex metabolic networks, this study used metabolomics and transcriptomics to analyze the different metabolites and genes of the strong desiccation resistance Cronobacter sakazakii CS 34 before and after drying treatment. It was found that betaine levels and genes related to its synthesis and transport were significantly upregulated posttreatment. This suggests that the betA gene may help Cronobacter resist dry environments by controlling betaine synthesis. To further explore this, betA/B gene knockout and complementation strains were constructed, and their growth and desiccation tolerance were assessed. Among them, the survival rate of betA, betB, and betAB knockout strains under dry conditions was significantly reduced. Observation using fluorescence microscopy and scanning electron microscopy showed that the cells of the knockout strain were damaged after drying and obvious holes appeared, and severe leakage of contents increased. Additionally, the knockout strains exhibited significantly higher levels of choline and lower levels of betaine compared with the wild-type strain. This indicated that choline is used for betaine synthesis, which ultimately aids C. sakazakii CS 34 in surviving in dry environments. In summary, this study elucidates the role of the betA, betB, and betAB genes in Cronobacter's desiccation resistance, providing valuable insights for reducing contamination of Cronobacter in powdered milk and reducing the probability of infection with Cronobacter in infants.